Effect of Heating at Various Temperatures for 30 Minutes on Pathogenicity of White Spot Syndrome Virus (WSSV) in Tiger Prawn (Penaeus monodon Fabr.) - D. Priatni; M. Alifuddin; D. Djokosetiyanto (Jurnal Akuakultur Indonesia)
White spot syndrome virus (WSSV) is a strong pathogenic virus which spread very rapidly and can cause tiger shrimp mass mortality within a short period.  Enhancement of shrimp immunity by infecting inactivated WSSV is one of the efforts to overcome WSSV infection in shrimp.  In this study, inactivated WSSV were prepared by heating them with various temperatures namely 45, 50, 55 and 60oC for 30 minutes. The results shows that infection with  heating inactivated WSSV at 45°C and 60°C for 30 min on PL-15 could increase their immunities.  The survival rate of inactivated WSSV-infected shrimp after challenge test with  WSSV virulent  reached 77%, while  no survive shrimp was observed in control.  This suggests that shrimp immunity could be improved by vaccination using  WSSV virus inactivated by heating.